Enterohemorrhagic Escherichia coli Effector Protein EspF Interacts With Host Protein ANXA6 and Triggers Myosin Light Chain Kinase (MLCK)-Dependent Tight Junction Dysregulation - Hua, Ying; Wu, Jiali; Fu, Muqing; Liu, Jinyue; Li, Xiaoxia; Zhang, Bao; Zhao, Wei; Wan, Chengsong (Frontiers in Cell and Developmental Biology, 2020)
Enterohemorrhagic Escherichia coli (EHEC) O157:H7 is an important foodborne pathogen that can cause bloody diarrhea and hemolytic uremic syndrome (HUS) in humans. EspF is one of the best-characterized effector proteins secreted from the type three secretion system to hijack host cell functions. However, the crucial pathogen-host interactions and the basis for the intestinal barrier disruption during infections remain elusive. Our previous study screened and verified the interaction between host protein ANXA6 and EspF protein. Here, by fluorescence resonance energy transfer (FRET) and co-immunoprecipitation (CO-IP), we verified that EspF interacts with ANXA6 through its C-terminal domain. Furthermore, we found that both the constitutive expression of EspF or ANXA6 and the co-expression of EspF-ANXA6 could decrease the levels of tight junction (TJ) proteins ZO-1 and occludin, and disrupt the distribution of ZO-1. Moreover, we showed that EspF-ANXA6 activated myosin light chain kinase (MLCK), induced the phosphorylation of myosin light chain (MLC) and PKCα, and down-regulated the expression level of Calmodulin protein. Collectively, this study revealed a novel interaction between the host protein (ANXA6) and EspF. The binding of EspF to ANXA6 may perturb TJs in an MLCK-MLC-dependent manner, and thus may be involved in EHEC pathogenic function.